Predicting the quality of a desired product in periodic technologies - Bol’shakov, V. I.; Volchuk, V.N.; Dubrov, Yu. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
It is shown that, for the prediction of the desired product quality in a batch technology, it is enough to apply statistical methods to evaluate the chemical composition of the starting material and to analyze the process conditions on the example of the production of rollers. To obtain reliable results under the production conditions, the use of the heuristic procedures during passive and active experimentations is proposed.